vicious Infants : Antisocial Childhoods And The Politics Of Population In Antebellum U.s. Literature - Soderberg, Laura Jean (2016)
Childhood as we now recognize it – innocent, vulnerable, and above all, precious – is deeply rooted in antebellum thought, when a culture of child worship drove much of sentimental politics and literature. Yet, this version of childhood does not begin to address the host of antebellum children who were never imagined as the future of the nation, except as a future to be warned against and avoided. At the same time that images of children as angels and treasures saturated U.S. culture, regulations binding children under systems of indenture, imprisonment, and slavery also took their greatest hold. This dissertation therefore offers a counter-history of childhood that focuses on its function as social threat in the antebellum United States, contending that conventional accounts of sentimental youth have overwritten other, less comforting models. Linking a variety of institutional literatures, such as law, medicine, and carceral theory, to literature by authors including Herman Melville, Harriet Wilson, Harriet Beecher Stowe, and Charles Brockden Brown, the dissertation argues that the antebellum period saw the rise of multiple modes of childhood governing a maturing subject’s trajectory towards or away from adult inclusion. These representations of childhood as antisocial serve to decouple the ideals of individual development and national inclusion, suggesting that children inhabiting a state were not inevitably its future citizens and could instead endanger its stability. Instead, it argues, these children came to represent sites for the imagination of alternative models of reproduction and group coherence